Madrasah Management Model in Langkat District Based on Islamic Spiritual Entrepreneurship - Muhammad Sadri; Faisar Ananda; Saparuddin Siregar (Budapest International Research and Critics University, 2021)
This study aims to identify and know the madrasa management model in Langkat District based on Islamic Spiritual Entrepreneurship. This model will be used as a madrasah management strategy in Langkat District for the continuation of madrasas in the future. This research is descriptive quantitative and explanatory research. The research instrument used was a questionnaire that was accompanied by a brief interview to the research respondents. The data used are primary data and secondary data. Then the data is processed using SEM (Structural Equation Modeling) analysis techniques using AMOS. The study population is all employees implementing or managing madrasa management in Langkat District with a sample of 300 respondents selected according to the SEM analysis standard chosen by accidental sampling technique. The results showed that the management of madrasa based on Islamic values (combined with the values of professionalism) was considered capable of supporting madrasah management and sustainability in the future. There are several factors that support the management of madrasa based on Islamic values, its known honest behavior as the most important factor, the concept of worship to Allah SWT, blessing factor from Allah SWT. But Islamic values (siddiq, amanah, tabligh and fathanah), thankful behavior do not have a significant effect because the measurement is difficult to objectively carry out because it is related to the individual character of a nature that not everyone can or does not want to be measured directly and openly. Therefore it is necessary to have character education, the existence of spirituality education for management managers and optimal management supervision.